Islamic Education and Social Media Literacy in Facing the Information Era for Indonesia’s Young Generation - Hilal Fikri , Lora (Journal of Education and Religious Studies, 2023)
This study examined the strategic role of Islamic education in enhancing social media literacy among young generations in the digital age. Using a qualitative approach through library research, the study explored how Islamic education could contribute to developing critical thinking skills, ethical behavior, and responsible use of social media platforms. The findings of the study highlighted three main roles of Islamic education: shaping character and attitudes aligned with Islamic values in social media usage, integrating learning materials on social media ethics, and fostering awareness of the impact of social media on personal development and society. Furthermore, the study identified key strategies for implementing social media literacy in Islamic education, including curriculum integration, utilizing social media as a learning tool, and developing critical thinking skills. The study concluded that Islamic education had significant potential in preparing young generations to face the challenges of the digital era by instilling Islamic principles such as tabayyun (verification), tadabbur (contemplation), and tabarruk (seeking blessings) in their online interactions. This holistic approach was expected to contribute to forming a generation of Muslims who were literate, critical, and responsible in their use of social media.